Analysis of Personal Development Process in Human Resource Management Training System (Case study: with emphasis on the development of education in the insurance industry) - mohammad hajpirouzbakht; Seyed Rasoul Hosseini; Mahmood Safari (Shahid Chamran University of Ahvaz, 2021)
AbstractThe purpose of this study was to design a training model for the insurance industry with an individual development approach in Tehran. The research method was qualitative hybrid method by grounded theory method and structural equation model by quantitative method. The research population in the quantitative section consisted of elite professors in planning in thirty educational and sample in the quantitative section were 163 experts of Atieh Sazan Hafez Company in Tehran in 1399.MethodThe method in this research was the method of exploratory theory and then analyzed by testing the structural equation model in pls the research tools were a semi-structured interview and a researcher-made questionnaire measuring the educational pattern with an individual development approach in insurance employees. The data were collected in the qualitative section by the grounded software basic categories such as branding capability and providing desirable services, improving psychological knowledge, basic and advanced research training. Results Finally, in both Shahabad and sampled plans, background factors and power relations play a role in the evolution of the concepts. The results showed that 10 components were identified. The results of the exploratory analysis showed improving the quality of educational processes, codified career guidance, learning culture, transparency and efficiency of the executive process, development technologically, development of motivation and transparent feedback system was achieved.Discussion Finally, the model showed good validity and fit. To monitor the achievement of goals and needs of personal development of employees and the movement of the program and training model in the right direction, the insurance organization needs to clarify the program and Their skill level will increase. The insurance organization can use experts in this field and the results of this research in the form of specialized workshops to plan appropriate training with its employees in a specialized and direct field for the development of individuals